Effects of distilled water and saline solution on the interlaminar shear strength of an aramidlepoxy composite - D'Almelda, J.R.M.
The effect of distilled water and saline solution upon the interlaminar shear strength (ILSS)of an aramid fibre-reinforced epoxy composite has been evaluated. Experimental results showed that the composite is affected by a similar degradation mechanism in both media. However, a greater absorption rate measured for specimens immersed in distilled water resulted in a faster decrease of ILSS values in distilled water than in salt water.
Keywords: COMPOSITE MATERIALS; WATER-ABSORPTION TESTS; INTERLAMINAR SHEAR; STRINGTH; ARAMID FIBRES; EPOXY RESIN